Key drivers of the TB epidemic in Suriname and priority actions to reduce incidence and mortality - E. Commiesie; D. Stijnberg; J. van den Boogaard; F. Gopie; S. Vreden; G. de Vries (IJTLD Open)
BACKGROUND: The WHO has recently published updated guidance for national strategic planning for TB. To address the TB epidemic comprehensively, it is necessary to conduct an epidemiological review as part of the situation analysis in the national strategic plan. METHODS: A descriptive epidemiological study was conducted using data from the national TB register for the period of 2010–2020. Simple frequencies were calculated for demographic and clinical variables. Trends in TB notification rates for the period 2010–2020 were also calculated. RESULTS: TB notification rates between 2011 (24.3/100,000) and 2019 (23.9/100,000) remained almost the same. The HIV status was known for 97.1% of TB cases, 22.7% of whom had HIV co-infection; 10.9% of patients with detected Mycobacterium tuberculosis were also resistant to rifampicin. Case fatality rate for all cases was 13.0%. Of the identified contacts, 66% were screened; 28.3–47.5% of those with TB infection started treatment, 63.3–75.9% of whom completed treatment. CONCLUSION: The review identified the following areas of concern: no decline in TB rates, high proportion of TB-HIV co-infection, high rate of resistance to rifampicin, high case-fatality rates and suboptimal contact investigation care cascade . The review was used to inform interventions and key actions to reduce TB morbidity and mortality in Suriname.